Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to solve the equation $$(3-\cos 4x)(\sin x - \cos x)=2.$$ I solve by putting $t = \sin x - \cos x$, but I can not find all solutions.

share|improve this question
    
The cosine expansion formula might help. –  Ben Oct 22 '12 at 1:15
    
Since solving the equation seems to be difficult, why not tell us how the equation arose. Maybe there's a way around it. –  Gerry Myerson Oct 22 '12 at 5:03

2 Answers 2

up vote 1 down vote accepted

Use $\sin x - \cos x = \sqrt{2}(\sin(x - \frac{\pi}{4}))$ followed by the substitution $x = y + \frac{\pi}{4}$. You get $(3+ \cos(4y))\sin y = \sqrt{2}$. This is satisfied if $\sin y = \frac{1}{\sqrt{2}}$. The equation $(3+ \cos(4y))\sin y = \sqrt{2}$ can be written as a fifth-degree polynomial in $\sin y$, and you know one of the roots, so you can get a fourth-degree polynomial.

share|improve this answer
    
And then what do you do with the $\cos4x$? –  Gerry Myerson Oct 22 '12 at 0:40
    
You substitute $x$ with $y + \frac{\pi}{4}$, as I said. I must apologize to the OP - I posted in haste and did not notice that this does not completely solve the problem. But it simplifies it. You will get a $\cos(4y)$, which can be expressed as a fourth-degree polynomial in $\sin y$. So the original equation can be transformed to a fifth-degree polynomial in $\sin y$. I can't think of anything better at the moment. –  Stefan Smith Oct 22 '12 at 0:44
    
@minthao_2011 : I plotted $(3+\cos(4y))*\sin(y)-\sqrt{2}$ from $0$ to $2\pi$ (see my answer above) in Maple and the only zeros were at $\frac{\pi}{4}$ and $\frac{3\pi}{4}$ (where $\sin y = \frac{1}{\sqrt 2}$). –  Stefan Smith Oct 22 '12 at 1:25
    
@minthao_2011 : See my answer above. Setting $Y = \sin y$, you get $4Y^4 - 2\sqrt{2}Y^3 - 2Y^2 -2\sqrt{2}Y + 1 = 0$. I plotted the left hand side of the equation in Maple from $Y = -1$ to $Y = 1$ and it was always positive, but unfortunately it got quite close to $0$. –  Stefan Smith Oct 22 '12 at 1:50

I have just a solution. \begin{equation*} (3-\cos 4x)(\sin x - \cos x) = 2. \end{equation*}

Note that, $3-\cos 4x > 0$, therefore $\sin x - \cos x>0$.

Put $t = \sin x - \cos x = \sqrt{2}\sin\left(x - \dfrac{\pi}{4}\right)$, and then $0<t \leqslant \sqrt{2}$. We have $$ t^2 = (\sin x - \cos x)^2 = 1 -\sin 2x.$$ Another way, $$3 - \cos 4x =3 - (1-2\sin^2 2x )= 2[1-(1-t^2)^2] = 2(t^4 -2t^2 + 2)$$ The given equation has the form $$2(t^4 -2t^2 + 2)t = 2,$$ equavalent to $$t^5- 2t^3+2t - 1 = 0.$$ Now we prove that this equation has only root $t = 1$.

First way. The function $f(t)=t^5 -2t^3 +2t - 1$ has $$f'(t) = 5t^4-6t^2+2>0, \forall t$$ Therefore, $f$ is an increasing function on the interval $(0; \sqrt{2}]$. And $f(1) = 0$, thus $t = 1$ is only root.

Second way, we have $$t^5- 2t^3+2t - 1 = 0 \Leftrightarrow (t-1)(t^4 +t^3 -t^2 -t + 1)=0.$$ Note that $$t^4 +t^3 -t^2 -t + 1 = \biggl(t^2 + \dfrac{t}2 -1\biggr)^2 + \dfrac{3t^2}4 > 0, \forall t.$$ Thirt way, we have $$t^4 +t^3 -t^2 -t + 1=0 \Leftrightarrow \biggl(t - \dfrac{1}{t}\biggr)^2 + \biggl(t - \dfrac{1}{t}\biggr) + 1 = 0. $$ The last equation has no sulution. With $t = 1$, we have $\sin x - \cos x = 1$, then $x = \dfrac{\pi}2 + k2\pi$ and $x = \pi + 2m\pi.$

share|improve this answer
    
@minthano_2011 : You solution improves on mine. –  Stefan Smith Oct 22 '12 at 13:16
    
How do you justify that the only solution of that 5th degree equation is $t=1$? –  Gerry Myerson Oct 23 '12 at 12:26
    
@GerryMyerson : see minthao_2011's solution above. $f'(t) = 5t^4 - 6t^2 + 2 > 0$ for all real $t$. –  Stefan Smith Oct 23 '12 at 14:02

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.